Self-Assessment of Undergraduate Medical Students Regarding the Clinical Knowledge in Forensic Medicine - Shrestha, Sugam; Gurung, Sharmila; Bhandari, Binus (Journal of Nepalgunj Medical College, 2022)
Introduction: Clinical forensic medical services play crucial role in emergency department followed by all other specialty.Aims: The preliminary survey was undertaken to assess the knowledge about the clinical forensic medicine among the medical students during their clinical posting in forensic medicine, Nepalgunj Medical College.Methods: The questionnaire was used in this study to evaluate the student’s knowledge.Results: As many as 108 medical students were included in the survey (70 male and 38 female). The maximum participants were 23 years old 38(35.2%) and youngest participant was 21 years old 6(5.6%). Maximum students were able to perform clinical forensic skills except traffic accident cases 27(25%) followed by gunshot wounds cases 46(42.6%). The students stated that they could master forensic pathology skills in asphyxia cases 80(74.07%) followed by dead victims in blunt and sharp violence cases 76(70.4%) and least in sudden death cases 31(28.7%), criminal abortion 43(39.8%), infanticide 45(41.7%) and sexual offences 49(45.3%). The students were able to issue medical certificate 99(91.7%) followed by issue a death certificate 98(90.7%) and provide information to the police 96(88.9%) but least could give expert statement 30(27.8%).Conclusion: In this survey, found the validity of student self-assessment in determining the ability of clinical knowledge, it is influenced by several factors of objectivity and subjectivity of assessment in terms of students.